SISTEM MONITORING SUHU DAN KELEMBABAN KANDANG AYAM BERBASIS INTERNET OF THINGS (IOT) - Novita Kurnia Ningrum; Tiara Widya Kusuma; Ibnu Utomo Wahyu Mulyono; Ajib Susanto; Yupie Kusumawati (Elkom : Jurnal Elektronika dan Komputer, 2023)
Broiler chickens are livestock whose growth is influenced by environmental temperature. The temperature of the chicken coop that is not suitable can affect the decrease in productivity and cause death in broiler chickens, so that the temperature setting of the cage must be considered. The design of this temperature and humidity monitoring system uses a nodemcu ESP8266 microcontroller and an arduino uno. If the measured temperature exceeds the set temperature limit, the system will send an SMS to the smartphone so that the cage officer can take appropriate action.